Case Report: Crosstalk between systemic lupus erythematosus and sickle cell syndromes—two cases from eastern India - Das, Dhriti Sundar (Frontiers in Lupus, 2024)
Autoimmune disease and sickle cell abnormalities are reported have some common pathogenic pathways. We describe two cases of sickle cell trait (SCT) presented with antibodies to antinuclear antigens and clinical features compatible with systemic lupus erythematosus (SLE). These patients were from eastern state of India i.e. Odisha. Both patients have documented sickle cell trait and positive for anti-double stranded DNA antibodies. Both patients presented with lupus nephritis without any obvious features of sickle cell hemoglobinopathies. Crosstalk between SLE and SCT may explain such association which needs validation in future large-scale studies.